2021
DOI: 10.1080/20002297.2021.2003617
|View full text |Cite
|
Sign up to set email alerts
|

Global proteomics of fibroblast cells treated with bacterial cyclic dinucleotides, c-di-GMP and c-di-AMP

Abstract: Background Constant exposure of human gingival fibroblasts (HGFs) to oral pathogens trigger selective immune responses. Recently, the activation of immune response to cyclic dinucleotides (CDNs) via STING has come to the forefront. Reports show that other proteins outside the STING-TBK1-IRF3 axis respond to CDNs but a global view of impacted proteome in diverse cells is lacking. HGFs are constantly exposed to bacterial-derived cyclic-di-adenosine monophosphate (c-di-AMP) and cyclic-di-guanosine mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Pathway analysis of DAC-induced genes also identified several processes related to interferon signaling and antiviral responses. While the functional consequences of this effect require further research, it should be noted that GF stimulation with bacterial cyclic dinucleotides results in the induction of a similar cluster of interferon signaling effectors, including ISG15 , MX1 , and IFIT1 ( 55 ). Finally, several DAC-inducible genes in GFs overlap with the transcription profiles observed in gingival biopsies from patients with chronic periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…Pathway analysis of DAC-induced genes also identified several processes related to interferon signaling and antiviral responses. While the functional consequences of this effect require further research, it should be noted that GF stimulation with bacterial cyclic dinucleotides results in the induction of a similar cluster of interferon signaling effectors, including ISG15 , MX1 , and IFIT1 ( 55 ). Finally, several DAC-inducible genes in GFs overlap with the transcription profiles observed in gingival biopsies from patients with chronic periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…The roles of c-di-AMP-mediated bacteria and host interaction in the occurrence and development of diseases are yet unclear. In previous investigations, researchers found that c-di-AMP could regulate the gingival epithelial cytokine response and affect critical processes of gingival fibroblasts, playing a substantial role in the pathogenesis of the periodontal disease (Elmanfi et al, 2018(Elmanfi et al, , 2020Onyedibe et al, 2021). More studies are needed to explore the regulatory effect of bacterial c-di-AMP on the immune microenvironment and the underlying mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…The protein abundance through proteomics enables the identification of the main proteins present in a sample and also differentially abundant proteins in different samples. Lately, proteomic analysis has been used widely in different challenged oral cells, tissues, and fluids, such as enamel [ 17 ], pulp [ 18 , 19 ], dental cementum [ 20 , 21 , 22 ], PDL [ 23 , 24 ], alveolar bone [ 22 ], periodontal ligament cells [ 25 , 26 ], gingival fibroblasts [ 27 ], gingival tissue [ 28 , 29 ], saliva [ 30 ], and gingival crevicular fluid [ 31 ], enabling researchers to better understand biological processes. Therefore, characterizing the PDL protein profile in obesity conditions becomes important in identifying possible biological markers different from those in health conditions.…”
Section: Introductionmentioning
confidence: 99%